2017
DOI: 10.18632/oncotarget.22661
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PACS-2 delays regeneration in DSS-induced colitis but does not affect the ApcMin model of colorectal cancer

Abstract: PACS-2 is a multifunctional sorting protein that mediates cell homeostasis. We recently identified PACS-2 in a functional genome-wide siRNA screen for novel regulators of the metalloproteinase ADAM17, the main sheddase for ligands of the ErbB receptor family. Of note, we showed that Pacs2-/- mice have significantly reduced EGFR activity and proliferative index in the intestinal epithelium. As EGFR signaling is highly mitogenic for intestinal epithelial stem cells, and plays essential roles in intestinal epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Ablation of PACS-2 in cells impairs the cell surface availability of TACE, reducing substrate cleavage ( Dombernowsky et al, 2015 ). However, PACS-2 has a relatively modest impact on TACE biology in vivo ( Dombernowsky et al, 2017 ), suggesting the possibility of unidentified trafficking regulators that may act separately from, or redundantly with, PACS-2.…”
Section: Introductionmentioning
confidence: 99%
“…Ablation of PACS-2 in cells impairs the cell surface availability of TACE, reducing substrate cleavage ( Dombernowsky et al, 2015 ). However, PACS-2 has a relatively modest impact on TACE biology in vivo ( Dombernowsky et al, 2017 ), suggesting the possibility of unidentified trafficking regulators that may act separately from, or redundantly with, PACS-2.…”
Section: Introductionmentioning
confidence: 99%
“…Our work illustrates iTAP as a physiological rheostat controlling TNF signalling and a novel target for the control of inflammation. (Dombernowsky et al, 2017), suggesting the possibility of unidentified trafficking regulators that may act separately from, or redundantly with, PACS-2.…”
mentioning
confidence: 99%
“…To answer this question, depletion of pacs2 in mice is a useful experimental model. PACS-2-deficient mice do not develop spontaneous neoplastic lesions in the intestine, and we recently reported that inactivation of one allele of the APC gene (ApcMin) – a commonly used model of human colon cancer – in PACS-2-deficient mice had no apparent consequence for adenoma development [ 3 ].…”
mentioning
confidence: 99%